Caring for people with early and advanced chronic obstructive pulmonary disease: how do family carers cope?. Issue 1 (2nd August 2013) - Figueiredo, Daniela; Gabriel, Raquel; Jácome, Cristina; Marques, Alda
<x xml:space="preserve">Abstract</x> Aims and objectives To examine the coping strategies of family carers of people with early and advanced chronic obstructive pulmonary disease and how those relate to their subjective health. Background Caring for a family member with chronic obstructive pulmonary disease can be a stressful experience. Understanding how carers cope with this is critical for improving outcomes. However, this topic has received little attention in the literature, particularly considering the care‐giving experience with early chronic obstructive pulmonary disease. Design A cross‐sectional study with a convenience sample of family carers of people with chronic obstructive pulmonary disease. Methods A structured questionnaire was used to collect data on socio‐demographics and care‐giving characteristics. Self‐rated physical and mental health was measured by two items from the International Classification of Functioning, Disability and Health checklist. Coping strategies were assessed with the Carers' Assessment of Managing Index. Descriptive and inferential analyses were performed. Results A total of 158 family carers participated: 109 caring for people with early and 49 with advanced chronic obstructive pulmonary disease. The two groups differed significantly on self‐rated mental health and on problem‐solving, emotional‐cognitive and managing stress coping type. Significant correlations between self‐rated physical health and problem‐solving coping and between self‐rated mental health and emotion‐cognitive and managing stress coping were found for carers of patients with advanced chronic obstructive pulmonary disease. Conclusions This study provides a unique insight into family carer coping strategies at different stages of chronic obstructive pulmonary disease. Carers of people with early and advanced chronic obstructive pulmonary disease cope differently with their caring demands. Nevertheless, problem‐focused coping strategies were perceived as the most helpful by both groups. Relevance to clinical practice The findings are relevant to informing early supportive interventions aiming to prevent burden and promote healthy adjustment to care‐giving demands within the specific context of chronic obstructive pulmonary disease.